Father Bear comes home. - Minarik, Else Holmelund; Sendak, Maurice ([New York] Harper, 1959)
Describes the adventures of Little Bear in which he goes fishing, has the hiccups, looks for a mermaid, and welcomes Father Bear home from the sea.
Keywords: Bears